POD02 Predicting brain atrophy at 1 year by baseline multimodal MRI data. Issue 11 (22nd October 2010) - Tarunya, A; Smith, S; Jenkinson, M; Palace, J A; Beckmann, C
Abstract : Background: In order to improve the sensitivity of neuroprotective trials in multiple sclerosis (MS) using brain atrophy measures we assessed whether it was possible to predict those patients who had high rates of change in brain volume. Methods: 22 primary progressive MS (PPMS) patients and seven healthy controls had multiple imaging measures assessed (total brain and regional volumes, cervical spinal cord area, single voxel spectroscopy of the corpus callosum (CC) and thalamus, diffusion tensor and magnetisation transfer imaging). Subsequent percentage brain volume change (PBVC) over 1 year was correlated with (a) baseline measures, (b) baseline measures adjusted for disease duration and estimated onset values to give a "prior rate of change" for each measure at baseline. Results: Only baseline CC volume was found to correlate using robust regression with PBVC (r=0.518 p=0.033). This correlation improved when an estimated prior rate of change in CC volume was used (r=0.624 p=0.01). A cut off of 2%/year loss in CC volume would have removed all patients who had subsequent PBVCs <1% and only exclude 2/11 (18.1%) of those who had PBVCs >1%. Conclusion: Baseline measures of the corpus callosum volume can preselect a subgroup of patients whose PBVC will be greater over the subsequent year. This baseline measure can be performed on the same image used to calculate subsequent PBVC. This could improve the efficiency in phase II neuroprotective trials in MS.